A Comparison Between Refusal Strategies In English Made By Indonesian Efl Students And Thailand Efl Students : An Interlanguage Pragmatic Study - Ilmiani, Dwi, Agus Wijayanto, Ph.D, Mauly Halwat Hikmat, Ph.D (2016)
This study deals with refusal strategies in English made by Indonesian EFL students (ILE) and Thailand EFL students (TLE). The aims of this study are (1) to analyze the differences and the similarities between refusal strategies made by both groups, (2) to analyze whether the two groups used similar or difference refusal strategies in social level, (3) and to analyze whether the two groups of speaker use the same or different politeness strategies in their refusals. The subjects of the research are 15 Indonesian EFL students and 15 Thailand EFL students who study at UMS. Refusal strategies to request and suggestion made by the two of groups became the object of this research. The type of this research is descriptive qualitative research. The data for this study is elicited from the respondents through the Discourse Completion Task (DCT) which consisted of six situations with different level status. The data were analyzed by Beebe et al refusal strategy and Brown and Levinson's politeness strategy. The finding of the study showed that ILE tended to be direct in declining a request and suggestion for examples, inability, unwillingness and direct 'no'. While TLE tended to employ 'excuse' almost in all DCT scenarios. It is also found that most of group participants used combination strategies of politeness in their groups. Key words: interlanguage pragmatic, refusal strategies, politeness strategies